The framing of the Belt and Road Initiative in Indo-Pakistani media - Jianxun Chu; Zameer Hassan; Syed Muhammad Sikandar (Humanities & Social Sciences Communications)
Abstract China’s Belt and Road Initiative (BRI) aims to revive ancient trade routes and boost international trade, enhancing regional integration, trade, and economic growth. The present study aimed to examine the representation of the BRI in Indo-Pakistani newspapers, specifically the Daily Dawn Pakistan and the Times of India, by employing computational framing analysis. A total of 2081 news reports from the Daily Dawn and 587 news reports from The Times of India were collected using the Lexis Advance database between March 23, 2013, and December 1, 2019. The findings revealed that the two newspapers utilized distinct framing strategies to represent the BRI. The Daily Dawn frames were related to development, security challenges, and political concerns, while India sees China as a strong opponent and the BRI as China’s geostrategic plan to extend its global power and military presence in the Indian Ocean, posing a challenge to India’s national interests. The results also indicated that bilateral talks, China-Pakistan Economic Corridor (CPEC) implications, and BRI concerns are the mainframes in the news coverage of The Times of India. This research provided qualitative evidence to study the media coverage of the BRI in Indo-Pakistani media. The results of this study can be a reference for policymakers and international players who seek to improve relations with both countries.